2016
DOI: 10.1093/neuros/nyw058
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Cervical Laminoplasty: Results at Two Years

Abstract: Laminoplasty with autograft is a safe and effective method to treat cervical myelopathy, with good medium-term clinical outcome. No reclosures were observed. Bony fusion was seen in all cases on CT scan. Our study found good outcomes in the performance of open-door laminoplasty without hardware, in the treatment of cervical stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The Nurick scores ranged from 3.16±0.9 preoperatively and improved to 1.94±0.8 at 2-year follow-up. The NDI improved from 28.7%±9% preoperatively to 20.8%±9.6% at final follow-up 43. An investigation into long-term follow-up for open-door laminoplasty for treatment of myelopathic patients with spondylotic disease or OPLL demonstrated good or excellent results in 59.3% and 55.0% of patients at 10 years, respectively.…”
Section: Surgical Management: Laminoplastymentioning
confidence: 87%
See 1 more Smart Citation
“…The Nurick scores ranged from 3.16±0.9 preoperatively and improved to 1.94±0.8 at 2-year follow-up. The NDI improved from 28.7%±9% preoperatively to 20.8%±9.6% at final follow-up 43. An investigation into long-term follow-up for open-door laminoplasty for treatment of myelopathic patients with spondylotic disease or OPLL demonstrated good or excellent results in 59.3% and 55.0% of patients at 10 years, respectively.…”
Section: Surgical Management: Laminoplastymentioning
confidence: 87%
“…The NDI improved from 28.7% ± 9% preoperatively to 20.8% ± 9.6% at final follow-up. 43 An investigation into long-term follow-up for open-door laminoplasty for treatment of myelopathic patients with spondylotic disease or OPLL demonstrated good or excellent results in 59.3% and 55.0% of patients at 10 years, respectively. The same study, however, did report up to 30% of patients experienced late deterioration in neurological function, particularly in patients over 70 years old.…”
Section: Surgical Management: Laminoplastymentioning
confidence: 99%
“…Recently, clinical studies in the literature have demonstrated that cervical laminoplasty has better clinical results than conventional laminectomy (5,20,40). Many laminoplasty procedures exist including en bloc cervical laminoplasty with acrocristectomy, the use of hydroxyapatite spacers, allograft, autograft, titanium miniplates-screws, or sutures (4,15,18,29,34). The techniques were successful in spinal cord decompression and very effective for (40).…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning, a thread was used to hold the lamina of the spinous processes. But lately, various forms of spacers were available, although some surgeons still not confident to use them and some still use autograft [4], [5], [6], [8]. The tendency to use mini-plates or hydroxyapatite spacer to maintain the opened side have emerged, with 53.1% of the studies reported the use of mini-plates or hydroxyapatite spacer.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons are still faced with some options regarding this procedure: using mini-plate without material for bone fusion, using materials such as hydroxyapatite bone-fusion, or using autograft with or without miniplate [6], [8]. Because of these choices, it is necessary to choose one device that is capable of carrying all the advantages stated above, easy to install, affordable, not adding foreign substances to the patient, ensuring bone fusion, sufficient to stabilise, not causing deformities, and does not cause neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%